Great at work how top performers do less, work better, and achieve more - Hansen, Morten T. (Simon & Schuster, 2018)
A book based on over two decades of research and an ongoing longitudinal study on individual performance that answers the question of why some people deliver exceptional perfomance and others, often despite innate talent or external forces, do not, and what these out-performers do differently